ANALISIS KEBUTUHAN SOFTWARE UNTUK SISTEM INFORMASI MANAJEMEN LAYANAN RSUD XYZ - Syafitri, Renny Diana; Susilowati, Meme; Kurniawan, Yudhi (Universitas Ma Chung, 2023)
RSUD XYZ is currently the only type B educational hospital at the middle level in Mojokerto Regency. The hospital faces challenges including suboptimal services in administration, payment, and health services, inadequate data integration, and minimal data-driven decision-making. To address these issues, there is a need to develop an information system that supports and facilitates daily operational activities. This research focuses on designing and compiling the Software Requirements Specification (SRS) documents for a Hospital Service Management Information System at XYZ Hospital, using the SDLC framework, specifically during the Planning, Requirement Analysis, and Design stages. The development follows the ISO/IEC/IEEE 29148:2018 (E) standard. The analysis has resulted in the creation of seven (7) modules: Outpatient & Emergency Registration, TPPRI, Cashier, Nursing Services, Medical Services, Pharmacy, and Medical Record Manager. Additionally, the research includes an analysis of the database design in terms of logical database requirements, user characteristics, and interface needs, in line with the ISO/IEC/IEEE 29148:2018 (E) standard.